Implementasi Standar ISO/IEC 29119 dalam Pengujian Kualitas Sistem Informasi Manajemen Inventori Berbasis Web - Muhamad Nurridwan; Ahmad Nurhidayat; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Web-based Inventory Management Systems simplify stock management, but their data integrity heavily relies on functional validation and system security. Objective: This study aims to conduct Quality Assurance (QA) testing on an open-source inventory management system using the ISO/IEC 29119 international standard to ensure functional reliability and data security. Methods: The testing methodology includes designing a Test Plan, creating 25 Test Cases, and identifying defects (Bug Reports) using Black Box Testing techniques. Results: The testing results show that the system successfully executes automated calculation functions (GST and discounts); however, 10 significant bugs were discovered, including critical vulnerabilities such as SQL Injection, Remote Code Execution via image uploads, and negative stock logic. Conclusion: While functionally adequate for basic needs, the system requires extensive server-side validation and security hardening before it can be implemented in a production environment.